Attracting investments through crowdfunding platforms as a method for agro-industrial enterprises to enter the international market - E. V. Nagovitsyna; D. S. Tusin (Вестник университета)
Since agriculture is an important sector of the Russian economy, the problem of lack of capital in this sector is still relevant. The article shows that in the era of digital technologies, new sources of fundraising are emerging in the agro-industrial complex. Crowdfunding is one of such modern sources of financing in the world practice which is able to significantly expand the basis of the investment pyramid of the agricultural sector. In the course of the study, a review of domestic and foreign literature on this method of raising funds was conducted. General scientific methods were used: observation, comparison, measurement, analysis and synthesis, the method of logical reasoning, and specific scientific method of static analysis. A critical review of domestic and foreign practice has shown the main advantages and disadvantages of attracting financing through crowdfunding platforms. Also, as a result of the conducted research, it was found that this way of attracting investments not only solves problems of financing the agricultural sector, but is also a successful method for agricultural enterprises to enter foreign markets. In the era of innovative finance, this article contributes to the growing literature and initiatives to introduce and develop crowdfunding in the agri-food industry.